2021
DOI: 10.1038/s41586-021-03655-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of missing data determined conclusions regarding moralizing gods

Abstract: The solid line indicates when writing and moralizing gods are first recorded in the same century, and the dashed lines show when writing appeared 100 years before moralizing gods and when moralizing gods appeared 100 years before writing.NGAs are colored by whether social complexity data are available both before and after the appearance of moralizing gods or not. Only NGAs with social complexity data available both before and after the appearance of moralizing gods were included in the analysis (and only thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 26 publications
(28 reference statements)
0
23
0
Order By: Relevance
“…However, there was no concrete evidence to suggest that the debate will arrive at a final conclusion. Until 7 July 2020 (which was when this paper was under review), Nature published two articles concerning the retraction of "Complex societies precede moralizing gods throughout world history": a Matter Arising article from Bret Beheim and his colleagues [31] and the retraction notice [16].…”
Section: The Seshat Debatementioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no concrete evidence to suggest that the debate will arrive at a final conclusion. Until 7 July 2020 (which was when this paper was under review), Nature published two articles concerning the retraction of "Complex societies precede moralizing gods throughout world history": a Matter Arising article from Bret Beheim and his colleagues [31] and the retraction notice [16].…”
Section: The Seshat Debatementioning
confidence: 99%
“…The Matter Arising article from Beheim et al [31] is the peer-reviewed version of the first criticism [19] toward the moralizing gods paper. Meanwhile, the retraction notice, which was written by the Seshat team, concluded that there are issues with the data treatment.…”
Section: The Seshat Debatementioning
confidence: 99%
“…For example, some maintain that "ancestral religions did not have a clear moral dimension" (Norenzayan 2013: 127) or that the world's traditional deities are somehow "weak" and/or "whimsical" (Chudek, Muthukrishna, and Henrich 2015). Others, however, challenge such positions and point to abundant evidence of moralistic supernatural punishment beliefs or traditions with "moral dimensions" in traditional societies (Beheim et al 2021;Bendixen et al 2021;Johnson 2014;2015;Lovins 2015;Purzycki 2011;Purzycki and Sosis forthcoming;Purzycki et al in press;Raffield, Price, and Collard 2019;Singh, Kaptchuk, and Henrich 2021).…”
Section: An Historical View Of Moralistic Godsmentioning
confidence: 99%
“…Two critical questions interwoven throughout these discussions are: How does the content of beliefs about and appeals to gods vary across groups and what accounts for this variation? While these questions have deep roots in the history of anthropological thought (e.g., Evans-Pritchard, 1965;Lang, 1909;Swanson, 1960;Tylor, 1920), the bulk of contemporary research mostly examines gods or religious traditions that are explicitly interested in human morality (Baumard et al, 2015;Beheim et al, 2021;Botero et al, 2014;Peoples and Marlowe, 2012;Roes and Raymond, 2003;Skoggard et al, 2020;Snarey, 1996;Watts et al, 2015). These studies primarily rely on-often the same-society-level data, usually from coded ethnographies and reports from travelers and missionaries (see Purzycki and Watts, 2018).…”
Section: Introductionmentioning
confidence: 99%